The use of recovery modalities by endurance runners - Lemke, Hanette (Department of Health and Rehabilitation Sciences, 2015)
Background: Overtraining and exercise-induced muscle injuries are common in endurance runners. A well-planned recovery protocol is crucial to limit fatigue and prevent injuries. There are multiple modalities available to aid the recovery process and facilitate optimal performance. However, there is limited information regarding the prevalence and pattern of use of recovery modalities in endurance runners, as well as the factors that may influence runners' decisions to use different recovery modalities. This information is important for the promotion of safe and effective use of recovery modalities and to identify potential educational requirements for athletes using recovery modalities. Aim and objectives: The aim of this study was to describe the use of different recovery modalities and regimes by endurance runners following training and races. The specific objectives of the study were: (a) to obtain information on recovery modalities used by endurance runners, such as the type of modalities, frequency of use, an d use during training and races; (b) to determine the factors that influence endurance runners when selecting recovery modalities; (c) to determine the knowledge endurance runners have of the perceived effectiveness of recovery modalities; (d) to explore associations between the use of recovery modalities in endurance runners and socio-demographic factors, such as, gender, age, body mass index, monthly income, level of education and training and competition history. Methods: This study had a descriptive correlation design. Adult runners who ha d been running for at least six months in the 12-month period preceding the study, and who were training a minimum of 30 km.wk -1 were included in this study. Participants who failed to provide informed consent or did not complete the mandatory sections of the questionnaire were excluded from the study. Participants were recruited at races and by contacting South African running clubs. Participants were required to complete a self-developed questionnaire that included demographic information, training and racing history, and the self-reported use of recovery modalities. The questionnaire was validated by a panel of experts. It was available in both hard copy and electronic format. Results: The study sample consisted of 433 participants (m ales 64%; females 36%), who were mostly well-educated with a tertiary degree or diploma. More than 80% of participants were predominantly road runners. Participants in this study reported using the twelve recovery modalities regularly, with passive recovery (90%), active recovery (76%) and stretches (67%) being the most commonly used modalities. Participants used a mean of 6 ± 2 different recovery modalities. All recovery modalities were commonly used during training and races, while cryotherapy, anti-inflammatory medication, contrast therapy, heat and massage were more commonly used after injury or for the management of pain. A protein supplement was used by 60% of participants, compared to 37% of participants' who reported using carbohydrate supplements. Between 10 % and 19% of participants did not know the proposed mechanism of action of different recovery modalities. Personal experience and information from fellow runners were the two main resources that influenced participants' use of different recovery modalities. Approximately 90% of participants reported that passive recovery and massage were effective recovery modalities, while over 30% of participants thought carbohydrates, compression, vitamins and minerals were less effective in assisting recovery from training and competition. Demographic factors such as gender, age, level of education and monthly income predicted the use of carbohydrates, protein, massage, anti-inflammatory medication, active recovery and compression. Training factors associated with more experience (for example number of marathons) predicted the use of vitamins and minerals, anti-inflammatory medication, active recovery and compression. The presence of a current injury predicted the use of cryotherapy, heat and contrast therapy. Conclusion In conclusion, this study showed there is widespread use of recovery modalities among endurance runners, despite the lack of evidence for their efficacy. Unsafe and inappropriate practices were identified, which may compromise performance, but may also place endurance runners at risk of serious adverse events during both training and competition. A major challenge is the strong influence of personal experience and information from fellow runners on the choice of recovery modalities. Educational initiatives, with a focus on peer-led education, are essential to encourage the safe and effective use of recovery modalities.